Pengaruh Latihan Sirkuit Training Terhadap Hasil Shooting SSB Cendrawasih FC Sidoarjo - Mufid Dwi Rosi Ardiansyah (Jurnal Ilmiah Adiraga, 2024)
This research aims to examine the shooting accuracy results at SSB Cendrawasih FC Sidoarjo. This research uses quantitative research with experimental methods. In this study, a one-group pretest-posttest design was used, where this design contained a pretest and posttest. The sample in this study were students who actively joined the SSB FC Cendrawasih Sidoarjo club, totaling 10 students. The implementation and collection of data in this research used the test method. The statistical analysis method used is descriptive analysis, normality test, and t test using SPSS 21. Based on the results of the t test using the SPSS version 21 application, it is known that the average (mean) value of the pretest and posttest results is -4.198 with a significance (2-tailed) of 0.002 <0.05. It can be concluded that circuit training exercises influence the results of SSB Cendrawasih FC Sidoarjo. Keywords: Shooting, Circuit training, Football.